Critical Care Nurses’ Knowledge about Pulmonary embolism in Respiratory Care Unit in Baghdad Teaching Hospitals (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim of the study: To asses the nurses’ knowledge about pulmonary embolismMethodology: A descriptive design study was carried out for the period of November18th 2018 up to the 20thof April 2019. Anon-probability (purposive) samples of (60) a nurse work at respiratory care unit in BaghdadTeaching Hospitals from different educational levels, both sexes ( males and females), were selected. Theinstrument questionnaire tool consist of two parts, First part consist of (6) items included, age, gender, levelof education, number of years of employment in hospital, number of experience in the respiratory care unitand training course about pulmonary embolism.& second part consist of (4) domains which included Nursesknowledge concerning definition and causes of disease, signs and symptoms, diagnostic test ,treatment ofpulmonary embolism. The data have been analyzed through the application of: descriptive and the inferentialanalysis, and the researcher used the SPSS version 20 to analysis of data.Conclusion: The study recommend that the critical care nurse have moderate level of knowledge andthere were significant association between level of education and the nurse knowledge at p > 0.05 level.
Keywords: Nurses’Knowledge, Pulmonaryembolism, Baghdad Teaching Hospitals.